(untitled) (Journal of Medical & Health Sciences Review, 2025)
Around the world, milk is an essential part of human diet. Although cow’s milk is the most often consumed, blended and alternative milk products are becoming more and more well-liked. This change calls for a thorough comprehension of their relative nutritional worth. In the dairy-rich district of Sargodha, Pakistan, this study sought to compare the nutritional makeup and physicochemical characteristics of commercially available mixed milk (MMS, probably cow plus buffalo) and cow’s milk (CMS). Using sterile procedures, twelve samples—six CMS and six MMS—were randomly selected from different parts of Sargodha. With the help of advanced analytical techniques, a qualified laboratory studied significant features of density, pH, freezing point, protein, lactose, fat, solids-not-fat (SNF), and salts. Statistically analysed using SPSS. The analysis revealed significant compositional differences. Mixed milk samples (MMS) contained a higher (4.37%-5.50) average fat content than cow milk (3.51%-5.13%). However, in case of SNF (8.84-10.27% vs. 8.10-9.16%), protein (3.86-4.39% vs. 2.90-3.64%), lactose (5.79-6.58% vs. 4.40-5.43%), and mineral salts (0.87-0.98% vs. 0.60-0.81%), the cow milk was always better than the mixed milk. Furthermore, cow milk was lower in freezing point and higher in density implying that the suture concentration was richer, and thus less was diluted. The researchers conclude that pure cow milk in the Sargodha region is nutritionally better, and there were significantly higher levels of protein, lactose and even minerals, despite the mixed milk being higher in fat. The reduced values of blended milk provide a potential source of processing or adulteration. These findings underline the importance of informed nutritional choices, especially in relation to the populations that are vulnerable and may require ideal nutrition, and the requirement of strict quality control in commercial milk products.